Thermodynamically induced in Situ and Tunable Cu Plasmonic Behaviour - Inwati, Gajendra Kumar (Sci Rep, 2018)
The Cu nanoparticles (Cu NPs) were grown in soda-lime glass matrix through Cu(+) ↔ Na(+) ion exchange methods under thermal annealing in an open environment and studied variation in their size on tunable plasmonic behaviour, optical absorption spectra and photoluminescence (PL). A blue shift from 570 to 560 nm was observed in localized surface plasmon resonance (SPR) of Cu NPs from 550 to 650 °C. A mutual relation between size and surface plasmon resonance with full width half maxima (FWHM) has been derived for plasmonic properties at variable temperatures. Structural investigations of embedded Cu NPs have been confirmed by using HRTEM and EDX. Grazing incidence X-ray diffraction (GIXRD) had identified a crystalline nature of Cu NPs under annealed conditions. XPS, Raman and secondary ion mass spectroscopies (SIMS) have identified an embedding behaviour of Cu NPs in glass matrix. Plasmonic and thermodynamic properties of embedded Cu NPs have explained their in situ thermal growth mechanism for efficient distribution where enthalpy (∆H), entropy (∆S) and Gibbs free energy (∆G) have interpreted their temperature driven Cu NPs growth. An interdependence of ∆H, ∆S and ∆G has been developed vis-a-vis activation energy on an extent of 12.54 J/mol.